2008
DOI: 10.1161/strokeaha.107.506097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Protocol for Acute Antifibrinolytic Therapy on Aneurysm Rebleeding After Subarachnoid Hemorrhage

Abstract: Background and Purpose--Aminocaproic acid (EACA) is an antifibrinolytic agent used to prevent rebleeding in aneurysmal subarachnoid hemorrhage. Although studies have found that a decrease in rebleeding with long-term antifibrinolytic therapy is offset by an increase in ischemic deficits, more recent studies have indicated that early, short-term therapy may be beneficial. Methods-We instituted a protocol for acute EACA administration starting at diagnosis and continued for a maximum duration of 72 hours after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
2

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(68 citation statements)
references
References 17 publications
5
61
0
2
Order By: Relevance
“…Such use led to a decreased incidence in rebleeding without increasing the risk of DCI, but 3-month clinical outcomes were not affected. 138 There was an increased risk of deep venous thrombosis but not pulmonary embolism. Neither aminocaproic acid nor tranexamic acid is approved by the US Food and Drug Administration for prevention of aneurysm rebleeding.…”
Section: Medical Measures To Prevent Rebleeding After Asahmentioning
confidence: 99%
“…Such use led to a decreased incidence in rebleeding without increasing the risk of DCI, but 3-month clinical outcomes were not affected. 138 There was an increased risk of deep venous thrombosis but not pulmonary embolism. Neither aminocaproic acid nor tranexamic acid is approved by the US Food and Drug Administration for prevention of aneurysm rebleeding.…”
Section: Medical Measures To Prevent Rebleeding After Asahmentioning
confidence: 99%
“…However, no study to date has been powered adequately to assess clinical outcome benefit with early short duration antifibrinolytic therapy. One study, however, has shown an increase in the rate of DVT's associated with the use antifibrinolytic therapy [25]. The Neurocritical Care Society's consensus statement on management of SAH recommends considering an initial early short course of an antifibrinolytic with early definitive treatment of the aneurysm [26].…”
Section: Immediate Managementmentioning
confidence: 99%
“…A prospective trial found that up to 72 hours of tranexamic acid substantially reduced the risk of aneurysm rebleeding with minimal thrombotic side effects (86). Aminocaproic acid use is also associated with a reduced risk of rebleeding (87).…”
Section: Specific Management Of Aneurysmal Subarachnoid Hemorrhagementioning
confidence: 99%